Complementary feeding practices in children aged 6-23 months: An institution-based observational study - Munde, Kshitij K.; Save, Sushma U. (Indian Journal of Child Health, 2021)
Background: Inappropriate complementary feeding practices in children may lead to adverse consequences ranging from growth failure to mortality. Intervention programs intending to optimize the practices should be based on identification of the lacunae and on the assessment of the magnitude of the problem. Aim: The aim of the study was to determine appropriateness and adequacy of complementary feeding given to children aged 6?23 months. Materials and Methods: Data regarding demographic profile, maternal education, source of information for feeding, and details of complementary feeding provided in the last 24 h were obtained from caregivers, using the standard WHO questionnaire. Chi-square test was used for determining the association between optimal feeding practices and continued breastfeeding, age-group, maternal education, and source of information. Results: The study enrolled 480 children (mean age: 12.9+5.1 month; male: female=1.22:1). 225 children (46.87%) had minimum meal frequency and 66 (13.8%) had minimum dietary diversity, 41 (11.08%) were receiving minimum acceptable diet. Only 103 mothers (21.5%) obtained the information regarding recommended complementary feeding practices from health professionals. There was a significant association between health professional being the source of information and presence of adequate dietary diversity (p<0.01) and minimum acceptable diet (p<0.01). Conclusion: Complimentary feeding practices are inadequate and thus, require an intervention of healthcare providers with better involvement.